2017
DOI: 10.1017/s1751731116002755
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of soil intake by growing Creole young bulls in common grazing systems in humid tropical conditions

Abstract: Soil is the main matrix which contributes to the transfer of environmental pollutants to animals and consequently into the food chain. In the French West Indies, chlordecone, a very persistent organochlorine pesticide, has been widely used on banana growing areas and this process has resulted in a long-term pollution of the corresponding soils. Domestic outside-reared herbivores are exposed to involuntary soil intake, and tethered grazing commonly used in West Indian systems can potentially favour their exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 28 publications
1
19
1
Order By: Relevance
“…2). This postgrazing sward height near to 14 cm seemed to be relatively high compared to the range of 3.3-8.2 cm reported in previous works 5,6 but the important differences in postgrazing vegetation structure (long lying stems vs. short erected ones) limiting the comparison of postgrazing sward heights with these studies. Indeed, animals grazed on the experimental plot until resource depletion and at D12 the remaining vegetation cover was only constituted of lying fibrous stems forming an 'insulating carpet' above the ground (Fig.…”
contrasting
confidence: 56%
See 2 more Smart Citations
“…2). This postgrazing sward height near to 14 cm seemed to be relatively high compared to the range of 3.3-8.2 cm reported in previous works 5,6 but the important differences in postgrazing vegetation structure (long lying stems vs. short erected ones) limiting the comparison of postgrazing sward heights with these studies. Indeed, animals grazed on the experimental plot until resource depletion and at D12 the remaining vegetation cover was only constituted of lying fibrous stems forming an 'insulating carpet' above the ground (Fig.…”
contrasting
confidence: 56%
“…3b and 3c). Previous studies conducted in tether-grazing growing bulls already reported a large range of variability in soil ingestions 5,6 ( Table 1). Given that in these experiments the animals presented similar age and BW, this interindividual variability can be attributed to differences in feeding behaviour between individuals.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Surface water, ground water, sediments and receiving coastal wasters have all been impacted. CLD has also been found to accumulate in animals [15][16][17] and plants used for food, including tubers and other vegetables grown in soil [18,19] as well as in marine fauna [9,20]. Effective methods to decontaminate soil and protect downgradient environments, food and water supply are clearly needed.…”
Section: Introductionmentioning
confidence: 99%
“…Among many important factors, soil minerals play an important role in sheep productivity and health status because sheep obtain their required nutrients from the feeds and fodder trees, which in turn derive in nutrients from the soil. During the grazing process, livestock intentionally or unintentionally ingest a small amount of soil, so a small amount of mineral elements from soil is directly consumed by the animals (Figure 1) [9]. The contribution of soil type and its nutritive composition of herbage can greatly contribute to the performance of live stock and are dependable in each environment [10].…”
Section: Introductionmentioning
confidence: 99%